2015
DOI: 10.1002/hbm.22799
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain changes underlying irritability in premanifest Huntington's disease

Abstract: The clinical phenotype of Huntington's disease (HD) consists of motor, cognitive and psychiatric symptoms, of which irritability is an important manifestation. Our aim was to identify the functional and structural brain changes that underlie irritability in premanifest HD (preHD). Twenty preHD carriers and 20 gene-negative controls from HD families took part in the study. Although the 5-year probability of disease onset was only 11%, the preHD group showed striatal atrophy and increased clinical irritability r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
(94 reference statements)
1
24
0
Order By: Relevance
“…It is possible that the pattern of hostility exhibited by HD monkeys is due to alterations in amygdala activity. Recent studies in HD patients have shown decreased amygdala activity during emotional tasks lending support for this hypothesis (Mason et al, 2015; Van den Stock, et al, 2015). Additionally, HD patients have also been shown to exhibit lower fear and higher anger ratings of fearful pictures as compared to healthy controls (Eddy, et al, 2011).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It is possible that the pattern of hostility exhibited by HD monkeys is due to alterations in amygdala activity. Recent studies in HD patients have shown decreased amygdala activity during emotional tasks lending support for this hypothesis (Mason et al, 2015; Van den Stock, et al, 2015). Additionally, HD patients have also been shown to exhibit lower fear and higher anger ratings of fearful pictures as compared to healthy controls (Eddy, et al, 2011).…”
Section: Discussionmentioning
confidence: 79%
“…Similar to anxiety, irritability has been seen prior to motor symptom onset in humans (Bouwens, et al, 2015; Van den Stock, et al, 2015). The current study used the Human Intruder task to examine the ability of HD monkeys to modulate their emotional response based on the salience of the threat present.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, PCC and PCUN respond strongly when people are asked to imagine emotionally hurtful events that may induce anger69. Finally, increased anger-selective activation has been found in the PCC and PCUN of participants with preclinical Huntington’s disease, of which irritability in an important manifestation70. In this context, the anger-specific functional integration of amygdala and brain stem, particularly with the pons, is a quite novel finding, though coherent with human and animal models or aggression.…”
Section: Discussionmentioning
confidence: 95%
“…Unseen facial and bodily expressions have yielded similar findings when presented in the blind fields of patients with affective blindsight. This indicates that a functional subcortical route to the Amg is invovled in emotion perception during sensory unawareness (Morris et al, 2001; de Gelder et al, 2005, 2011; Pegna et al, 2005; Tamietto and de Gelder, 2010; Van den Stock et al, 2011a,b, 2013, 2015a; Georgy et al, 2016). The involvement of the superior colliculus and pulvinar is in keeping with their connectional pattern and physiological properties.…”
Section: Pathways To the Amg Relevant For Non-conscious Emotion Percementioning
confidence: 94%
“…On the one hand, Amg activity contingent upon sensory and attentional awareness in healthy as well as brain damaged patients has emerged from the use of non-facial stimuli, thereby extending evidence of non-conscious emotion processing to other stimulus categories. Bodily expressions of emotions, both static and dynamic, have been the most extensively studied non-facial stimuli (de Gelder and Hadjikhani, 2006; de Gelder et al, 2006, 2010; Tamietto et al, 2009; Van den Stock et al, 2011a,b, 2013, 2015a,b; Tamietto et al, 2015). Visual stimuli associated to danger in our evolutionary past, such as snakes and spiders, have also been studied during attentional and sensory unawareness.…”
Section: Stimulus Categories and Properties Triggering Amygdala Respomentioning
confidence: 99%